Uncertainties and Dynamic Connectedness Among Sectors: A Case of the USA, India, France, Germany and Russia - Ashok Kumar Mishra; Pradiptarathi Panda; Subhendu Kumar Pradhan; Ajaya Kumar Panda; Ciorstan Smark (Australasian Accounting, Business and Finance Journal, 2024)
This study examines the connectedness among the sectoral indices for the USA, India, France, Germany and Russia stock markets pre and post-COVID-19. We use the Diebold and Yilmaz spillover index to examine the study's objectives. This study finds that volatility spillover is higher during COVID-19 than before COVID-19. In addition, the volatility transmission across the sectors demonstrated mixed results regarding net volatility receivers and transmitters. However, the degree of transmission is higher for the net volatility receivers than for the net volatility transmitters. This study will help policymakers draft related policies to immunise their economy and market from spillover contagions of international markets during varying pandemic scenarios. This study would also help potential investors, including foreign institutional investors, diversify their portfolios based on the sectors with net volatility transmitters and receivers.
Keywords: USA; India; France; Germany; Russia; Sectoral Spillovers; COVID-19. Stock markets; Diebold; Yilmaz Index